2015
DOI: 10.1172/jci82357
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio following preconception low-dose aspirin in women with prior pregnancy loss

Abstract: alter the sex ratio of pregnancies among women with a history of pregnancy loss, given the sex-dependent embryonic effects of maternal inflammation.BACKGROUND. Several lines of evidence suggest that male embryos may have greater vulnerability than female embryos to disordered inflammation; therefore, antiinflammatory drugs, such as low-dose aspirin (LDA), may alter the sex ratio. Here, we assessed the effect of LDA on male live birth and male offspring, incorporating pregnancy losses (n = 56) via genetic asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Most embryos are lost between the time of fertilization and clinical recognition of the pregnancy, and if chronic inflammation affects embryogenesis (perhaps through epigenetic processes), the sex ratio at birth may be skewed (19). This hypothesis is supported by a recent study showing that higher levels of high-sensitivity C-reactive protein prior to conception were associated with a lower likelihood of having a live-born male child (9).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most embryos are lost between the time of fertilization and clinical recognition of the pregnancy, and if chronic inflammation affects embryogenesis (perhaps through epigenetic processes), the sex ratio at birth may be skewed (19). This hypothesis is supported by a recent study showing that higher levels of high-sensitivity C-reactive protein prior to conception were associated with a lower likelihood of having a live-born male child (9).…”
Section: Discussionmentioning
confidence: 94%
“…A skewed sex ratio could be due to specific characteristics of SLE or may be a general consequence of the associated chronic inflammatory state. A recent study showed that higher levels of inflammation in women were associated with a reduced number of male offspring, and that the sex ratio was restored by treatment with low‐dose aspirin . Because this concept has not been well substantiated in the clinic, we sought to estimate the male‐to‐female ratio among deliveries to women in a large population‐based cohort, comparing women with SLE and those with rheumatoid arthritis (RA) (another systemic inflammatory disease) with women in the general population.…”
mentioning
confidence: 99%
“…Male gender as a gestational risk factor was also reported by Radin et al [21] who investigated the effect of preconception intake of low-dose aspirin (LDA) on male live birth. They followed two groups of women with prior pregnancy loss: one group was treated with daily intake of LDA, and the second group was treated with placebo.…”
Section: Gender-related Effects In Biology and In Teratology 41 Gendmentioning
confidence: 59%
“…Thus, in a prespecified secondary analysis of the EAGeR trial 65 to investigate the impacts of LDA therapy on offspring sex ratio, LDA was shown to increase male live births overall (RR: 1.31, 95% CI: 1.07, 1.59) and had no effect on female live birth. A further analysis found a similar positive effect of LDA on pregnancy with male offspring by including the outcome of pregnancy with a male embryo, whether the pregnancy ended in live birth or loss.…”
Section: Inflammation and Implantationmentioning
confidence: 99%
“…Karyotype or microarray determined the offspring sex from pregnancy losses. 65 To further evaluate the hypotheses that inflammation was hazardous to male embryos, and that LDA was subsequently protective, the analysis was stratified by hsCRP level at study entry. Congruent with the findings of the stratified analysis of LDA and live birth, the percentage male at birth decreased with increasing tertile of hsCRP among the placebo group, but the proportion of males remained at the expected level among the LDA-treated group (►Fig.…”
Section: Inflammation and Implantationmentioning
confidence: 99%